2013
DOI: 10.1016/j.febslet.2013.01.067
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response of microglial BV‐2 cells includes a glycolytic shift and is modulated by mitochondrial glucose‐regulated protein 75/mortalin

Abstract: Recent studies suggest a link between mitochondria and proinflammatory cytokine generation. We previously demonstrated that overexpression of mitochondrial chaperone glucose-regulated protein75 (Grp75/mortalin) protects mitochondria. In this study we investigated the modulation of the lipopolisaccharide (LPS)-induced inflammatory response of microglial BV-2 cells by Grp75. We demonstrate that LPS-induced activation promotes significant metabolic changes suppressing mitochondrial function and increasing glycoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
153
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(168 citation statements)
references
References 35 publications
14
153
1
Order By: Relevance
“…Other reports suggest that regulation of LPS-induced mitochondrial ROS is involved in the pro-inflammatory response of BV-2 microglia cells via NF-B activation [7,22]. We, therefore, examined whether mitochondrial ROS affect the LPS-induced MAPK and NF-B signal pathways by using Mito-TEMPO.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Other reports suggest that regulation of LPS-induced mitochondrial ROS is involved in the pro-inflammatory response of BV-2 microglia cells via NF-B activation [7,22]. We, therefore, examined whether mitochondrial ROS affect the LPS-induced MAPK and NF-B signal pathways by using Mito-TEMPO.…”
Section: Discussionmentioning
confidence: 97%
“…Apart from serving as an antimicrobial defense in microglia cells, ROS are key factors in immune cell signaling [15]. Mitochondrial ROS are implicated in the pro-inflammatory responses of microglia cells [7,22]. In addition, various treatments that induce mitochondrial ROS result in enhanced activation of inflammation transcription factors [6,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the overall levels of ROS can be effectively reduced by eliminating superoxide. Activated microglia produce superoxide predominantly from NADPH oxidase, although ROS generation from mitochondria has also been reported (10,11). Of note, once ROS are generated anywhere within cells, further ROS generation is induced via uncoupling of the mitochondrial respiratory chain, known as ROS-induced ROS release (46).…”
Section: Discussionmentioning
confidence: 99%
“…Copper chloride has been shown to stimulate mitochondrial superoxide production in murine BV-2 microglial cells (10). Lipopolysaccharide (LPS), an endotoxin found in the outer membrane of Gram-negative bacteria, also elicits mitochondrial superoxide production, which is regulated by the mitochondrial chaperone glucose-regulated protein 75 (Grp75/mortalin) (11). Naik and Dixit (12) suggested that alterations in the redox environment of the plasma membrane could cause mitochondrial ROS formation.…”
mentioning
confidence: 99%